PENINGKATAN KESADARAN MASYARAKAT DALAM MENERAPKAN PERILAKU HIDUP BERSIH DAN SEHAT - Anggi Dwiyanto; Teofilus Ardian Hopeman; Fitriani Setiawan; Areska Areska; Lusi Lusi (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service has been carried out from August to September 2022 in Cikahuripan Village, Cisolok District, Sukabumi Regency. Some of the main problems in Cikahuripan Village are not yet optimal public awareness not to litter, especially throwing garbage in the river. This service aims to increase public awareness of environmental hygiene and health through education and technology. The service is carried out in the form of a seminar entitled "Socialization on the Application of Healthy and Clean Living Behavior" The seminar was held in elementary schools aimed at instilling the importance of cleanliness in the community from an early age, as well as by making automatic trash cans to increase interest in disposing of waste in its place. After the service is completed, it is hoped that the level of concern for some people towards environmental cleanliness and health can continue to increase. In addition, by making trash cans, it is hoped that creativity can continue to grow, especially in the field of technology.Keywords: Environment, Education, Technology